In Vitro Antimicrobial Activity of Eichornia crassipes and Pistia stratiotes Extracts as Natural Disinfection Agents - Kaidah, Siti; Budiarti, Lia Yulia; Azhari, Nazla Puteri; Ihsanti, Shofia Hilwa (MAGNA MEDIKA Berkala Ilmiah Kedokteran dan Kesehatan, 2024)
Background:  Eichornia crassipes and Pistia stratoites are aquatic weeds that contain various antimicrobial compounds and have the potential to disinfectants. Objective: This study aims to analyze the antimicrobial activity of extract of Eichornia crassipes and Pistia stratoites as In Vitro disinfection agentsMethods: This in vitro experimental study tested E.crassipes and P.statoites extracts in combined (EC+PS)  forms against several species of bacteria and Candida albicans. The testing of antimicrobial activity using the diffusion method and effectiveness as a disinfectant were tested through the phenol coefficient test. Results: The results of the data analysis of the EC+PS 25%-100% (ratio 1:1) treatment using the ANOVA test and Duncan's posthoc (significance 95%), obtained different inhibition zones for gram-positive, gram-negative bacteria, and C.albicans; EC100%+PS100 extract produced the widest inhibition zone. The inhibitory power of EC+PS extracts ranged from moderate to strong (> 5 mm - > 20 mm). In the phenol coefficient test using a dilution of 1:20-1:250, a good coefficient value (> 1) was obtained from the EC+PS extract treatment and the disinfectant control for all test organisms.  Conclusion: E.crassipes and P.stratoites extracts can produce antimicrobial activity with a good phenol coefficient value, which makes their combination a natural disinfectant.